(untitled) (Global Journal of Medical Research, 2022)
Objectives 1 To assess the role of MRI in the diagnosis and staging of Avascular necrosis of the femoral head 2 To evaluate the demographic profile with emphasis on risk factors for AVN 3 To evaluate the most common quadrant of the femoral head affected in AVN 4 To analyze the MRI findings in AVN of the femoral head Methods This single-center retrospective observational study was conducted in the department of radiodiagnosis in a tertiary care institute situated in an urban area 70 patients of all age groups with clinical suspicion of AVN were evaluated over a period of one and a half years between January 2020 to June 2021 Of these 6 patients with osteoarthritis were excluded with 64 patients included in this study Demographic and clinical details with particular emphasis on risk factors and relevant lab parameters were collected from records and reviewed for all patients Scans were performed on 3-Tesla MRI scanner Seimens SkyraTM Ficat and Arlet classification was used to stage the disease